Business environment, spatial spillover, and urban–rural income gap——an empirical test based on provincial panel data in China - Zhao, Tongtong; Jiao, Fangyi (Frontiers in Environmental Science, 2022)
With economic development, the global ranking of China's business environment has been greatly improved, however, the cost of rapid economic development is a growing disparity in income among urban-rural areas. As a result, investigating the impact of the business environment on the urban-rural income gap is critical to determining how to narrow the urban-rural income gap and achieve common prosperity. This paper collects and organizes data from 31provinces in China from 2011 to 2019, as well as provides an analysis of optimizing the business environment on the urban-rural wealth divide using the Durbin spatial model and adjacent spatial weight matrix. The accompanying three results are presented from this survey: (1) The outcomes of the spatial Durbin model discovered that there is a spatial spillover effect on the business environment, and optimizing the business environment not only reduces the regional urban-rural income gap but also has an impact on the regional urban-rural wage crevice in neighboring regions; (2) Through the use of empirical analysis methods to test the different dimensions of the business environment, it is found that the overall impact of the product market development, non-state economy development, market intermediary development, and legal system have a significant spatial spillover effect on reducing urban and rural income inequality; (3) Deeper research finds that there is regional heterogeneity in the effect of improving the business environment on the urban-rural wage hole. Only the central provinces have a significant spatial business environment spillover effect, while there is no significant business environment spillover effect in the eastern and western provinces. China should further accelerate the construction of the business environment, which is of great importance to lessen the disparity in wealth between urban-rural.